HDL particle morphology in Alzheimer’s disease patients compared to healthy human subjects and chemically modified HDL - Zheng, Jack Jingyuan; Hong, Brian V.; Agus, Joanne; Guo, Fei; Cavicchi, Richard E.; Jin, Lee‐Way; Maezawa, Izumi; Lebrilla, Carlito B.; Harvey, Danielle J.; Zivkovic, Angela M. (Alzheimer's & dementia, 2021)
Background In various chronic diseases including Alzheimer’s disease, a common clinical manifestation is defective high‐density lipoprotein (HDL) status. Published evidence suggests that HDL particles from Alzheimer’s patients are functionally deficient, as measured by impaired cholesterol efflux capacity. However, the structural and compositional alterations of HDL particles that contribute to this loss of function in Alzheimer’s disease are currently not well understood. Method In this study, we investigated the morphological characteristics of HDL particles from 7 patients confirmed with Alzheimer’s disease and 3 age‐matched healthy subjects using transmission electron microscopy. We also analyzed how oxidation, glycation, deglycosylation, and acidification alter the morphology of HDL isolated from healthy human subjects and compared these chemically treated HDL with HDL from Alzheimer’s patients and controls. Result Distinct treatment‐specific variation patterns of HDL particles, including particle size change, aggregation, and disintegration, were observed. Most prominently, HDL incubated at a pH of 5.5 for 18 hours had an increased average HDL particle diameter from 10.65 ± 2.22 nm to 13.08 ± 2.77 nm (P<0.001). In addition, both glycation and oxidation treatment caused HDL to form aggregates. HDL isolated from patients with Alzheimer’s disease and age‐matched, cognitively normal subjects displayed aggregate structures that resembled those of chemically glycated and oxidized HDL. These aggregated HDL structures were found in both patients and controls. Conclusion Further studies with larger sample sizes are needed to better characterize the morphological, structural, and compositional alterations that cause the loss of HDL function in patients with Alzheimer’s disease.